Radiological differentiation of phaeochromocytoma from other malignant adrenal masses: importance of wash-in characteristics on multiphase CECT. Issue 7 (July 2019) - Goroshi, Manjunath; Jadhav, Swati S; Sarathi, Vijaya; Lila, Anurag R; Patil, Virendra A; Shah, Ravikumar; Hira, Priya; Sharma, Rajaram; Goroshi, Shettepppa; Fernandes, Gwendolyn; Rojekar, Amey; Dalvi, Abhay; et al.
Abstract : Rationale and introduction: To evaluate the computerised tomography (CT) characteristics of phaeochromocytoma (PCC) that differentiate them from other non-benign adrenal masses such as adrenocortical carcinoma (ACC), primary adrenal lymphoma (PAL) and adrenal metastases (AM). Methods: This retrospective study was conducted at a tertiary health care institute from Western India. Patients presented between January 2013 and August 2016 with histological diagnosis of PCC or other non-benign adrenal mass having adequate reviewable imaging data comprising all four CECT phases were included. Results: The study cohort consisted of 72 adrenal masses from 66 patients (33 PCC, 22 ACC, 4 PAL, 13 AM). Unlike other masses, majority of PCC (25/33) showed peak enhancement in early arterial phase (EAP). PCC had significantly higher attenuation in EAP and early venous phase (EVP), and higher calculated percentage arterial enhancement (PAE) and percentage venous enhancement (PVE) than other adrenal masses ( P < 0.001). For diagnosis of PCC with 100% specificity, PAE value ≥100% and EAP attenuation ≥100 HU had 78.8 and 63.6% sensitivity respectively. ACC were significantly larger in size as compared to PCC and metastasis. The adreniform shape was exclusively found in PAL (two out of four) and AM (4 out of 13). None of the enhancement, wash-in or washout characteristics were discriminatory among ACC, PAL and AM. Conclusion: Peak enhancement in EAP, PAE value ≥100% and EAP attenuation ≥100 HU differentiate PCC from other malignant adrenal masses with high specificity.